Antifungal potential of biosurfactants produced by strains of Bacillus spp. (Bacillales: Bacillaceae) selected by molecular screening - Olmedo, Camila (2022)
Introduction: Bacillus species are used as biological controllers for phytopathogenic fungi, and the mechanisms to produce controllers include biosynthesis of lipopeptide biosurfactants with antifungal activity. Objective: To evaluate the antifungal potential of the biosurfactants produced by Bacillus strains, selected by molecular screening, on Fusarium oxysporum. Methods: We selected four molecular markers, related to the biosynthesis of surfactin, fengicin, and lichenysin (srfA, spf, fenB, LichAA) in nine Bacillus strains. We used two mineral media with several culture conditions, for biosurfactant production, and a well diffusion test for antifungal potential. Results: Only the biosurfactant produced by UFAB25 inhibits the mycelial growth of F. oxysporum (44 % ± 13): this biosurfactant was positive for srfA, spf, and fenB genes involved in the synthesis of surfactin and fengicine. Antifungal activity depends on culture conditions and the strain. Conclusions: Genetic markers are useful to detect strains with antifungal potential, facilitating the selection of bio-controllers. The biosurfactant profile is influenced by the strain and by culture conditions.